Engaging male students with mental health support: a qualitative focus group study - I. Sagar-Ouriaghli; J. S. L. Brown; V. Tailor; E. Godfrey (BMC, 2020)
Abstract Background Males are less likely to seek help for mental health difficulties compared to females. Despite considerable interest, a paucity of evidence-based solutions exists to address this. Concerns about students' mental health has led to the United Kingdom's Department of Education to make this a priority. Studies have shown that male students hold more negative attitudes towards the use of psychological services compared to female students and are less likely to seek help. A major concern is that male students make up 69% of university suicides, which is often associated with lower rates of help-seeking. This focus group study therefore sought to identify potential approaches that would be relevant to improving mental health help-seeking in male students. Methods Three focus groups comprising of 24 male students at a London University were conducted. Participants were asked questions exploring: the barriers to seeking help, what would encourage help-seeking, how an appropriate intervention should be designed, and how to publicise this intervention to male students. Thematic analysis was conducted to evaluate participants responses. Results Five distinct themes were identified. These were: 1) protecting male vulnerability, 2) providing a masculine narrative of help-seeking, 3) differences over intervention format, 4) difficulty knowing when and how to seek help, and 5) strategies to sensitively engage male students. Conclusions These themes represent important considerations that can be used, together with the existing literature about male help-seeking, to develop more male friendly interventions that are suitable for male students. This could help improve help-seeking attitudes and the uptake of mental health interventions for male students experiencing emotional distress.